Gender Identity and The Sacredness of The Hijab: Value Conflicts in Contemporary Muslim Societies - Setiadi, Fadlan Masykura; Alsalih, Ayat (UIN Sulthan Thaha Saifuddin Jambi, 2025)
This research aimed to explore the meaning of hijab from traditional and modern perspectives, as well as analyze the controversy related to its use by transgender individuals in the context of religion and gender identity. This research employed a qualitative approach based on literature review and case study, as well as Durkheim's sacredness theory and queer theory as analytical frameworks. The results showed that the hijab undergoes a transformation of meaning from a mere religious obligation to a more inclusive social symbol, triggering debates between conservative and more inclusive groups in Muslim society. The case of Isa Zega, a transgender woman who wore the hijab during Umrah, became a critical point in the discussion about the limits of the sacredness of the hijab and individual rights in spiritual expression. While some consider the use of hijab by transgender people as a violation of religious norms, others see it as a form of spirituality that is not limited to gender categories. This debate reflects the tension between established religious understandings and the dynamics of gender identity in modern society. Therefore, a more open dialogue is needed between scholars, academics, and the wider community to find a balance between Islamic teachings and inclusivity values, so that the hijab remains a meaningful and relevant symbol in various social contexts.